PEREMAJAAN KAWASAN PASAR BAUNTUNG BANJARBARU (REDEVELOPMENT) - Heldasari, Heldasari; Anhar, Pakhri (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
Banjarbaru Bauntung Market is a market that has been established since 1965 which until now has experienced an increase in the number of traders, especially street vendors. This market is located on Jalan Lanan, right in the center of Banjarbaru City. Bauntung market is experiencing a decline which can be seen from the buildings and facilities inside that are not maintained. In addition, due to the increase in street vendors, zoning and circulation in this market are irregular. The right architectural problem solving for the Banjarbaru Bauntung Market, namely, the redevelopment of the Banjarbaru Bauntung Market Area which accommodates the needs of users (traders and buyers) by adjusting the dawn market, activities, zoning, and circulation, as to make a clean, safe, and comfortable market area. Programmatic architectural methods to achieve a clean, safe, and comfortable market by focusing on market activities at dawn, zoning, and circulation are the preferred approaches used in solving architectural problems in the Bauntung Banjarbaru Market. This is manifested in the circulation arranged according to use, optimal zoning both inside and outside, and dawn market activities that are easier to manage.